Low-Level Versus High-Level Equilibrium in Public Utility Services - Strand, Jon (2012)
Heterogeneity of public utility services is common in developing countries. In a "high-level" equilibrium, the quality of utility services is high, consumer willingness to pay for services is high, the utility is well funded and staff well paid in order to induce high quality of performance. In a "low-level" equilibrium the opposite is the case. Which alternative occurs depends on both the quality of utility management, and public perceptions about service quality. If a utility administration has the potential to offer high-quality service, and the public is aware of this, high-quality equilibrium also requires the public s service payments to be high enough to fund the needed pay incentives for the utility staff. When the public lack knowledge about the utility administration s quality, the public s initial beliefs about the utility administration s quality also will influence their willingness to make adequate service payments for a high-quality equilibrium. This paper shows that, with low confidence, only a low-level equilibrium may exist; while with higher initial confidence, a high-level equilibrium become possible. "Intermediate" (in between the low- and high-level) outcomes also can occur in early periods, with "high-level" outcomes later on.